Institutional Conditioning of the German Labour Market in the Face of the Global Economic Crisis 2008-2009 - Michal Moszynski (Institute of Economic Research (IER), 2015)
The scientific objective of this study is an attempt to clarify the institutional aspects of the functioning of the labour market in Germany that are relevant to the response to the crisis of 2008-2009. After a brief review of the selected institutions in Germany in comparison to the OECD countries, the labour market reforms undertaken in the period between 2002 and 2007 will be discussed. Then, selected on the basis of literature studies, institutional buffers of the labour market mitigating shocks are examined with particular emphasis on the instruments of internal flexibility, social partners' behaviour and institutional connections of labour markets with other domains of economic order. The elements of institutional framework are subject to qualitative analysis backed up by available official statistical data.
Keywords: E24; H12; J52; A11; A14; B16; 330; crisis; Germany; labour market institutions; employment; unemployment